Therapeutic inhibition of cathepsin S reduces inflammation and mucus plugging in adult βENaC-Tg mice - Brown, Ryan; Small, Donna M.; Doherty, Declan F.; Holsinger, Leslie; Booth, Robert; Williams, Richard; Ingram, Rebecca J.; Elborn, J. Stuart; Mall, Marcus A.; Taggart, Clifford C.; Weldon, Sinéad (Mediators of inflammation, 2021)
Background. Elevated levels of the cysteine protease cathepsin S (CatS) are associated with chronic mucoobstructive lung diseases such as cystic fibrosis (CF) and chronic obstructive pulmonary disease (COPD). We have previously demonstrated that prophylactic treatment with a CatS inhibitor from birth reduces inflammation, mucus plugging, and lung tissue damage in juvenile β-epithelial Na+ channel-overexpressing transgenic (βENaC-Tg) mice with chronic inflammatory mucoobstructive lung disease. In this study, we build upon this work to examine the effects of therapeutic intervention with a CatS inhibitor in adult βENaC-Tg mice with established disease. Methods. βENaC-Tg mice and wild-type (WT) littermates were treated with a CatS inhibitor from 4 to 6 weeks of age, and CatS-/-βENaC-Tg mice were analysed at 6 weeks of age. Bronchoalveolar lavage (BAL) fluid inflammatory cell counts were quantified, and lung tissue destruction and mucus obstruction were analysed histologically. Results. At 6 weeks of age, βENaC-Tg mice developed significant airway inflammation, lung tissue damage, and mucus plugging when compared to WT mice. CatS-/-βENaC-Tg mice and βENaC-Tg mice receiving inhibitor had significantly reduced airway mononuclear and polymorphonuclear (PMN) cell counts as well as mucus plugging. However, in contrast to CatS-/-βENaC-Tg mice, therapeutic inhibition of CatS in βENaC-Tg mice had no effect on established emphysema-like lung tissue damage. Conclusions. These results suggest that while early CatS targeting may be required to prevent the onset and progression of lung tissue damage, therapeutic CatS targeting effectively inhibited airway inflammation and mucus obstruction. These results indicate the important role CatS may play in the pathogenesis and progression of mucoobstructive lung disease.